Cost-Effectiveness of Screening for Primary Aldosteronism and Subtype Diagnosis in the Resistant Hypertensive Patients. (November 2015) - Lubitz, Carrie C.; Economopoulos, Konstantinos P.; Sy, Stephen; Johanson, Colden; Kunzel, Heike E.; Reincke, Martin; Gazelle, G. Scott; Weinstein, Milton C.; Gaziano, Thomas A.
Abstract : Background—: Primary aldosteronism (PA) is a common and underdiagnosed disease with significant morbidity potentially cured by surgery. We aim to assess if the long-term cardiovascular benefits of identifying and treating surgically correctable PA outweigh the upfront increased costs in patients at the time patients are diagnosed with resistant hypertension (RH). Methods and Results—: A decision-analytic model compares aggregate costs and systolic blood pressure changes of 6 recommended or implemented diagnostic strategies for PA in a simulated population of at-risk RH patients. We also evaluate a 7th "treat all" strategy wherein all patients with RH are treated with a mineralocorticoid-receptor antagonist without further testing at RH diagnosis. Changes in systolic blood pressure are subsequently converted into gains in quality-adjusted life years (QALYs) by applying National Health and Nutrition Examination Survey data on concomitant risk factors to an existing cardiovascular disease simulation model. QALYs and lifetime costs were then used to calculate incremental cost-effectiveness ratios for the competing strategies. The incremental cost-effectiveness ratio for the strategy of computerized tomography (CT) followed by adrenal venous sampling (AVS) was 82 000/QALY compared with treat all. Incremental cost-effectiveness ratios for CT alone and AVS alone were 200 000/QALY and 492 000/QALY; the other strategies were more costly and less effective. Integrating differential patient-reported health-related quality of life adjustments for patients with PA, and incremental cost-effectiveness ratios for screening patients with CT followed by AVS, CT alone, and AVS alone were 52 000/QALY, 114 000/QALY, and 269 000/QALY gained. Conclusions—: CT scanning followed by AVS was a cost-effective strategy to screen for PA among patients with RH. Abstract : Supplemental Digital Content is available in the text.